Poly (vinyl alcohol)/chitosan/sodium alginate composite blended membrane: Preparation, characterization, and water-induced shape memory phenomenon - Yang, J.-M. (John Wiley and Sons Inc, 2022)
In this study, we successfully prepared poly (vinyl alcohol)/chitosan/sodium alginate blended (PCS/SA) composite membranes by a simple solution casting method and solvent evaporation technique. The physicochemical properties and effect of different wt of sodium alginate (SA) on poly (vinyl alcohol)/chitosan (PCS) membranes were systematically evaluated and studied along with its shape memory properties and mechanism. With increased wt of SA, the crystallinity of PCS/SA membranes reduced significantly. PCS/SA membrane has better thermal stability than pure PVA membrane but is slightly lower than PCS membrane and decreased with higher SA contents. Dynamic mechanical analysis (DMA) study revealed that water act as a stimulus for the shape recovery behavior. The mechanical study showed that PCS membranes with a small amount of SA (0.1 and 0.2Â wt) have a much better elongation at break than other membranes. The swelling ratio, gel contents, and contact angle results concurred with the results of shape memory effect (SME) of all membranes, where the PCS with higher contents of SA possess better and faster shape recovery speed. The above results demonstrate that SA is a potential additive that can be used for water-induced shape memory applications. Â© 2022 Society of Plastics Engineers.